Daya Tarik Museum Batam Raja Ali Haji sebagai Destinasi Wisata Budaya - Sinaga, Dora (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2022)
Museums as a cultural tourism destination have a special attraction for tourists. In its development, the museum has become part of a tourism package which is the medium of communication for visitors to know the history and culture of an area visited. Museums must have attractiveness as tourist destinations. This study aims to examine the Raja Ali Haji Museum as one of the cultural and historical tourist destinations in Batam city. This research refers to the facilities, collections, and accessibility of the museum. The method used in this research is qualitative-descriptive by collecting data through written information and interviews. The analysis technique used is the SWOT technique. What has been obtained from the study is that the Raja Ali Haji Museum has a unique structure in its roof and building construction. It also has interesting collections of Malay culture and the history of Batam City. Its location is strategic in that it is easily accessible for anyone to visit the museum. These factors make this museum to be suitable to be a tourist destination. However, it needs to increase the number of its collections and provide web virtual tours as a source of information for tourists who might not be able to visit the museum in person.